أثر الجودة المؤسسية السياسية على جاذبية الإستثمار الأجنبي المباشر للجزائر خلال الفترة (1996-2020) - بوقرة, مبروك; بوصنوبرة, علي (جامعة الوادي - University of Eloued, 2022)
This research paper aims to investigate the impact of political institutional quality on attracting foreign direct investment to Algeria during the period (1996-2020), depending on the method of the Autoregressive Model with Decelerated or Distributed Time Gaps (ARDL), and using the governance indicators issued by the World Bank, which reflects the quality of the institutional political. After testing the study model, it was concluded that there is a long-term relationship between political institutional quality indicators and foreign direct investment flows, where the results showed the positive and important long-term effects of each of the political stability index, organizational quality, and corruption index on these flows, while the rule of law index negatively affects those flows. This is consistent with the study of (Pesaran, 2001 & all., PP. 289-326).
The impact of political institutional quality on the attractiveness of FDI to Algeria during (1996-2020)
مقال
Keywords: الجودة المؤسسية السياسية؛ مؤشرات الحوكمة؛ جاذبية المناخ الإستثماري؛ مؤشر الإستقرار السياسي،; Political institutional quality; Governance Indicators; Attractive Investment Climate; Political Institutional Quality.